The Relationship Between Anemia in Pregnancy and Premature Rupture of the Membranes (PROM) - Muthoharoh, Husnul; Fajrin, Fitriana Ikhtiarinawati; Kurniawati, Indah; Adyani, Asta (Jurnal MIDPRO, 2023)
Anemia in pregnancy is a condition with a hemoglobin (Hb) level of < 11 g% which is characterized by complaints of weakness, dizzy eyes , paleness, and even palpitations. Anemia is one of the factors that causes Premature Rupture of The Membrans (PROM). Mothers who experience anemia, the iron or hemoglobin which is a carrier in the blood will decrease, which results in fragility in several parts of the amniotic membrane, which at the same time causes leakage in the area. This study aims to determine the relationship between anemia in pregnancy and the occurrence of PROM. This study uses the design method study Observational Descriptive , Correlation Analytical Research Method with Retrospective Approach . The data source was obtained from all pregnant women at the gestational age of TM II and III who carried out pregnancy checks at the Maduran Health Center, Maduran Village, Maduran District, Lamongan Regency, at 12 Februari 2023 – 12 Mei 2023 with a total population of 31 people. The sampling technique used purposive sampling . Statistical tests used Chi-Square and data were analyzed using the Fisher Exact Test . Based on the results of the study, the majority of respondents who experienced anemia as many as 16 respondents (51.6 % ). The majority of respondents who experienced PROM were 19 respondents ( 61.2 %), while the majority of respondents who experienced anemia and PROM were 14 respondents ( 45.1% ) . The conclusion of this study is that there is a relationship between anemia in pregnancy and the incidence of premature rupture of membranes (PROM) at the Maduran Health Center, Maduran Village, Maduran District, Lamongan Regency with a p-value (0.001).